Temporal bone meningiomas: emphasizing radiologic signs to improve preoperative diagnosis - Zeleník, Karol; Hanzlíková, Pavla; Blatová, Barbora; Formánek, Martin; Komínek, Pavel (European archives of oto-rhino-laryngology, 2021)
PURPOSE: Temporal bone meningioma is an extremely rare disease. Lack of clinical attention due to its rarity might lead to delayed diagnosis. This short communication aims to emphasize radiologic signs of temporal bone meningiomas to improve preoperative diagnosis. METHODS: Radiological characteristics of temporal bone meningiomas are discussed. RESULTS: Temporal bone meningioma is characterized by diffuse "hairy" trabecular hyperostosis without the destruction of trabecular structures, bone thickening, and irregular surface margins of the temporal bone on computed tomography. The dural tail sign is a unique feature of temporal bone meningioma on magnetic resonance imaging. CONCLUSION: Otolaryngologists certainly should be aware of characteristic radiologic signs of temporal bone meningiomas. Using modern computed tomography and magnetic resonance imaging protocols enables with a high degree of accuracy to distinguish temporal bone meningiomas from other more common entities in this location.
Keywords: Meningeal Neoplasms; meningeom; Trabecular hyperostosis; Magnetic Resonance Imaging; Humans; Computed tomography; spánková kost; lidé; Magnetic resonance imaging; Meningioma; magnetická rezonanční tomografie; Dural tail sign; Temporal Bone; Diagnosis; Temporal bone meningioma; meningeální nádory; Tomography, X-Ray Computed; počítačová rentgenová tomografie